Modifikasi Platform Kunci Algoritma Playfair Untuk Meningkatkan Nilai Confusion Pada Ciphertext - Rivalri Kristianto Hondro (Journal of Computer System and Informatics (JoSYC), 2020)
Cryptography is the science of "original manuscript" encoding techniques, called plaintext terms, the arrangement of which is encrypted using a key so that it becomes "random text that is difficult to read" or referred to as ciphertext. By doing this process, someone who does not have a decryption key cannot read the original data. The cryptographic application technique is often also called the Algorithm or Cipher, one of the cryptographic algorithms discussed in this article is the Playfair Algorithm. Modifications are made to the key table that is owned by the Playfair Algorithm so that there are additional characters besides letters, there are numbers and symbols. The result to be achieved is from the modification of the Playfair algorithm that can be applied to the encryption process so as to produce a ciphertext that has a confusion value. but it can also be applied to the decryption process so as to produce an understandable plaintext